Implementasi Program Kreativitas Mahasiswa Kewirausahaan (PKM-K) Melalui Inovasi Olahan Ikan Tongkol Menjadi Produk Sambal Khas Lokal - Nirmala, Dea; Kusuma, Anindita Suliya Hangesti Mandra; Septiana, Alya; Komalasari, Baiq Resti; Fitri, Dea Nirmala; Nuradelia, Debby; Ardiana, Baiq Mis (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Samtodenis or the abbreviation for Sweet Spicy Tongkol Sambalis a PKM-K product made by students withmade from chili sauce and tuna which has a distinctive aromaa combination of selected spices and without the use of ingredientspreservative. The aim of this PKM-K samtodenis is to find outmanufacturing process, marketing process, development method as wellfind out the benefits of sweet and spicy tuna chili sauce on an ongoing basis.The method for making samtodenis starts from the process of cleaning the fishcob, chili sauce preparation process, processing process andpackaging of cob chili sauce to the marketing process. OpportunitySamtodenis marketing starts with boarding house children, housewives andIt can be consumed by everyone from children to the elderlyMarketing strategies are carried out using a sales marketing systemdirect and indirect sales. Results from promotions andmarketing carried out, the PKM-K team succeeded in selling the productas many as 238 bottles with 7 production times over 2 months andget income of IDR 3,570,000 so the total profit isobtained is IDR 770,000. Based on cash flow analysisfor 2 years, the NPV value of "SAMTODENIS" production was obtained for2 year period with a value of IDR 12,433,563,635. The NPV valueshows that this business is worth implementing and continuing.